Scanning pulsed laser ablation in liquids: An alternative route to obtaining biocompatible YbFe nanoparticles as multiplatform contrast agents for combined MRI and CT imaging. Issue 6 (15th March 2023) - Felix, Eduardo; Mánuel, José M.; Litrán, Rocio; Rodríguez, Miguel A.; Román-Sánchez, Sara; Lahoz, Ruth; Natividad, Eva; Fernández-Ponce, Cecilia; Garcia-Cozar, Francisco; Llaguno-Munive, Monserrat; Abasolo, Ibane; Yeste, Pilar; et al.
Abstract: Ytterbium ferrites are being used in many promising applications, such as visible-light photocatalysis, solar cells, magnetooptic devices, electro-magnetic equipment, etc., due to their fantastic ferroelectric and ferromagnetic properties. However, despite their good magnetic and radiopaque features, the use of ytterbium ferrites as multiplatform contrast agents in magnetic resonance imaging (MRI) and X-ray computed tomography (CT) is still under-developed. This is mainly due to difficulties in obtaining stable and biocompatible aqueous colloidal dispersions of ytterbium ferrite nanoparticles. In order to overcome this limitation, this work explores an eco-friendly method to directly synthesize such dispersions by liquid-assisted pulsed laser ablation of ytterbium ferrite massive targets. First, orthorhombic bulk YbFeO3 targets were obtained by a reaction-sintering method. Then, colloidal dispersions of nanoparticles were produced directly in both distilled water and ethanol by irradiating the bulk YbFeO3 targets with high-power infrared nanosecond lasers pulses. A battery of techniques has been used to characterize the as synthesized YbFeO3 targets and colloidal dispersions of YbFe nanoparticles to determine their composition, structure, magnetic properties, X-ray attenuation potentials, and colloidal properties. Moreover, the biocompatibility of the systems was also analysed by MTT cell viability assay. Results indicated that the use of distilled water as ablation medium yields colloidal dispersions consisted mainly of paramagnetic ytterbium ferrite nanoparticles. Contrarily, the use of ethanol as solvent leads to colloidal dispersions of polycrystalline nanoparticles with both ferromagnetic and paramagnetic behaviour, due to the coexistence, in each nanoparticle, of ytterbium ferrite, ytterbium oxide, and iron oxide crystalline phases. Both colloidal dispersions exhibit also high biocompatibility and suitable X-ray attenuation properties. Moreover, they show bio-safe hydrodynamic sizes (lower than 200 nm) with acceptable overall hydrodynamic polydispersity index values (under 0.4), being stable in water for several weeks. These results pave the way for the future evaluation of Yb–Fe based nanoparticles as multiplatform contrast agents in multimodal MRI and CT imaging. Graphical abstract: Image 1